Prognostic significance of tumor-infiltrating lymphocytes in predicting outcome of distal cholangiocarcinoma in Thailand - Intarawichian, Piyapharom; Sangpaibool, Sirada; Prajumwongs, Piya; Sa-Ngiamwibool, Prakasit; Sangkhamanon, Sakkarn; Kunprom, Waritta; Thanee, Malinee; Loilome, Watcharin; Khuntikeo, Narong; Titapun, Attapol; Jareanrat, Apiwat; Thanasukarn, Vasin; et al. (Frontiers in Oncology, 2022)
Patients with distal cholangiocarcinoma (dCCA) generally have poor outcomes because of late presentation and diagnosis. Therefore, prognostic factors for predicting outcomes are essential to improve therapeutic strategies and quality of life. Tumor-infiltrating lymphocytes (TILs) have been reported as a prognostic predictor in several cancers. However, their role in dCCA is still unclear. This study aimed to evaluate the association of TILs with outcome in patients with dCCA. Fifty-two patients were evaluated for the percentage rate of TILs in their cancers, and a median TIL level was used to divide the patients into two groups. Survival, multivariate, and correlation analyses were performed to determine the prognostic factors. Results showed that a low TIL level was associated with poor survival. Multivariate analysis revealed TILs as an independent factor for poor outcome. Moreover, TILs were markedly correlated with growth patterns, and both were applied to classify patients with dCCA. Subgroups of TILs with growth pattern incorporation improved stratification performance in separating good from poor patient outcomes. This study suggested that TILs could be a prognostic factor for predicting survival and for clustering patients with dCCA to improve prognostication capability. This finding may be incorporated into a new staging system for stratifying dCCA in Thailand.